2012
DOI: 10.1007/s11357-012-9416-8
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K7 and GSTZ1 are associated with human longevity: a two-stage case–control study using a multilocus genotyping

Abstract: The pathways that regulate energy homeostasis, the mechanisms of damage repair, and the signaling response to internal environmental changes or external signals have been shown to be critical in modulating lifespan of model organisms and humans. In order to investigate whether genetic variation of genes involved in these pathways contribute to longevity, a two-stage case-control study in two independent sets of long-lived individuals from Calabria (Italy) was performed. In stage 1, 317 SNPs in 104 genes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Hence, the finding of HSD17B8 as a hub gene strengthens the hypothesis of a regulatory role in androstenone synthesis. GSTZ1 was found as a hub gene in the lightgreen module and as a DE gene in liver which encodes a member of the GSTs 95 . Other hub genes included SERPINC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the finding of HSD17B8 as a hub gene strengthens the hypothesis of a regulatory role in androstenone synthesis. GSTZ1 was found as a hub gene in the lightgreen module and as a DE gene in liver which encodes a member of the GSTs 95 . Other hub genes included SERPINC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are crucial enzymes in anti-aging processes. For example, mitochondrial protein levels of the GSTK1 and GSTM4 are significantly higher in dwarf mice and are regulated by growth hormones [28]; GSTK1 is implicated in the cellular response to internal and external environmental changes, playing a crucial role in the inflammation processes that accompany aging [33]. Aging affects the metabolic capacity of GSTZ1 to detoxify Dichloroacetate (DCA) [34], and GSTs are crucial enzymes in the cell detoxification process catalyzing the nucleophilic attack of GSH on toxic electrophilic substrates and to produce a less dangerous compound, especially by alpha and mu classes of GST [32], and the zeta class of GST received more attention from a therapeutic perspective [31].…”
Section: The Theta Class Of Gstsmentioning
confidence: 99%
“…A high level of oxidative stress is also an important risk factor of other age-related diseases such as hypertension, atherosclerosis, and diabetes. SNP (single nucleotide polymorphisms) studies have identified Tp53, coding for tumor suppressor p53 [140,141,142], EXO1 [143], GPX1 (glutathione peroxidase1) [144], SOD2 (manganese superoxide dismutase) [145], heat shock proteins genes HSPA1A, HSPA1B, and HSPA1L [146,147,148], GSTZ1 (glutathione S-transferase zeta 1) [149], NOS1, NOS2 (nitric oxide synthase 1 and 2) [150], and UCPs (uncoupling proteins) [147,151,152] as susceptibility genes.Genes involved in telomeres length: they have been found to be associated with human longevity such as TERT and TERC (telomerase reverse transcriptase, telomerase RNA component) [153], SIRT1, and SIRT3 (sirtuins) [154,155]. The first discoveries were made in yeasts and tetrahymena by Elizabeth Blackburn, finding the role of TERT and TERC ([156] and references within).…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been replicated in other model organisms [161], but their role in longevity is not consistent for all species, and therefore is still under debate [162]. Genes involved in metabolism and cellular division: APOE (apolipoprotein E) [163], TXNRD1 (thioredoxin reductase 1), XDH (xanthine dehydrogenase) [163], MAP3K7 (mitogen-activated protein kinase kinase kinase 7) [149], AKT kinase, and TOR [164]. The association of APOE with human longevity have been replicated in different populations: [165,166,167].…”
Section: Discussionmentioning
confidence: 99%